2020
DOI: 10.3892/etm.2020.8730
|View full text |Cite
|
Sign up to set email alerts
|

Combination of sufentanil, dexmedetomidine and ropivacaine to improve epidural labor analgesia effect: A randomized controlled trial

Abstract: Opioids and α2-agonists have been used as epidural adjuvants in local anesthetics for a long time, but the effect of the combination of opioids and α2-agonists as epidural adjuvants is not completely understood. In the present study, the combination of dexmedetomidine (Dex) and sufentanil as adjuvants to ropivacaine for epidural labor analgesia was investigated. A total of 108 parturient women receiving labor epidural analgesia were randomly divided into three groups: i) Group RD received 0.1% ropivacaine + 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…Comparison of our present data with other literature is rather difficult, as most of the published studies have studied the two adjuvants separately using different drug administration protocols or concentrations. However, similar trends were seen in studies based on dexmedetomidine as well as clonidine [15][16][17][18].…”
Section: Discussionsupporting
confidence: 74%
“…Comparison of our present data with other literature is rather difficult, as most of the published studies have studied the two adjuvants separately using different drug administration protocols or concentrations. However, similar trends were seen in studies based on dexmedetomidine as well as clonidine [15][16][17][18].…”
Section: Discussionsupporting
confidence: 74%
“…Eight RCTs assessing ropivacaine were carried out in China [ 3 , 11 , 22 27 ], and one assessing bupivacaine was carried out in Egypt [ 21 ]. Five studies [ 3 , 11 , 22 , 25 , 27 ] compared dexmedetomidine with placebo, one [ 21 ] compared dexmedetomidine with fentanyl, and three [ 23 , 24 , 26 ] compared dexmedetomidine with sufentanil. Six RCTs [ 3 , 22 26 ] used 0.5 μ g/mL dexmedetomidine, one [ 11 ] used 0.5 μ g/kg dexmedetomidine, one [ 21 ] used 1 μ g/kg dexmedetomidine, and one [ 27 ] used four concentrations of dexmedetomidine.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 3 , 11 , 22 , 25 , 27 ] compared dexmedetomidine with placebo, one [ 21 ] compared dexmedetomidine with fentanyl, and three [ 23 , 24 , 26 ] compared dexmedetomidine with sufentanil. Six RCTs [ 3 , 22 26 ] used 0.5 μ g/mL dexmedetomidine, one [ 11 ] used 0.5 μ g/kg dexmedetomidine, one [ 21 ] used 1 μ g/kg dexmedetomidine, and one [ 27 ] used four concentrations of dexmedetomidine. Eight studies [ 3 , 11 , 21 , 23 27 ] with Jadad scores ≥4 were regarded as of high-quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 In contrast to opioids, dexmedetomidine has been used safely and effectively for epidural labor analgesia without increasing the incidence of adverse effects. 6–12 Consequently, it can be recommended that dexmedetomidine is used as an epidural adjuvant instead of opioids in some clinical circumstances, especially for parturients with opioid intolerance. Previous studies have reported the appropriate doses of epidural dexmedetomidine used for labor analgesia, whereas the optimal dose is unknown.…”
Section: Introductionmentioning
confidence: 99%